2013
DOI: 10.3109/01913123.2013.790527
|View full text |Cite
|
Sign up to set email alerts
|

Rats on a High-energy Diet Showing No Weight Gain Present with Ultrastructural Changes Associated with Liver Fibrosis

Abstract: Sibutramine is widely used as a weight-loss substance in the treatment of obesity and is a selective inhibitor of the neuronal reuptake of serotonin and noradrenaline. Although banned it is often a hidden ingredient in herbal and dietary supplements which are widely used by the general public. Various weight loss products, including sibutramine, have successfully been tested in animal models of diet-induced obesity. In the female Sprague-Dawley rat model, fed a high-energy diet that did not produce a significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…Sibutramine has been shown to cause liver fibrosis in rats fed a HE diet without weight gain (Oberholzer et al, 2013). This was based on morphological analysis of liver tissue which showed an observable increase in collagen deposition and lipid accumulation within hepatic stellate cells, which have been shown to increase extracellular matrix production following liver injury (Moreira, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sibutramine has been shown to cause liver fibrosis in rats fed a HE diet without weight gain (Oberholzer et al, 2013). This was based on morphological analysis of liver tissue which showed an observable increase in collagen deposition and lipid accumulation within hepatic stellate cells, which have been shown to increase extracellular matrix production following liver injury (Moreira, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In such a model, using Sprague-Dawley rats, Jackson et al, (1997) described the hypophagic effects of Sibutramine and identified the key adrenoreceptors and serotonergic receptors involved in its pharmacological mechanism. In a study to determine the safety of Sibutramine it was observed that, following Sibutramine 3 administration, ultrastructural changes in morphology associated with fibrosis in liver tissue in Sprague-Dawley rats fed a high energy diet that did not result in weight gain, could be observed by Oberholzer et al (2013). In this study the effects Sibutramine on lung morphology was further investigated by using light-and transmission electron microscopy.…”
Section: Introductionmentioning
confidence: 96%
“…It is indispensable for maintaining life and has multiple functions, including glycogen storage, protein synthesis, hormone synthesis, and detoxification [ 3 , 4 , 5 ]. Various biotic factors (bacteria, viruses), abiotic factors (chemical drugs, physical damage), and unhealthy lifestyles (high-energy diet, binge drinking) can cause liver injury and induce chronic liver diseases [ 6 , 7 , 8 , 9 ]. Many chronic liver diseases gradually progress to liver fibrosis, liver cirrhosis, or hepatocellular carcinoma, ultimately leading to irreversible hepatic lesions [ 10 , 11 ] ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%